Effects of different pretreatments on the pore structure of Chinese yam during microwave freeze drying - Wang, Hui; Duan, Xu; Zhao, Lujie; Duan, Liuliu; Ren, Guangyue (International Journal of Agricultural and Biological Engineering, 2020)
In order to explore the effects of different pretreatments on the pore structure of Chinese yam during Microwave Freeze Drying (MFD), the samples were treated by typical drying pretreatments including osmosis, blanching and ultrasound, and compared with the untreated samples. The results showed that the pretreatment had significant impacts on the porosity of MFD Chinese yam. Ultrasonic pretreatment could obtain the highest open porosity, and the internal pore network structure of the material showed a uniform sponge shape. The shape of pores obtained by blanching pretreatment was the most irregular. The pore network structure obtained by different pretreatments could result in various product texture and rehydration, which implied that pretreatment methods should be carefully selected according to actual requirements. All these pretreatments could improve the open porosity of MFD Chinese yam, which result in a better rehydration capability. Among them, ultrasonic treatment is worth further investigating. Keywords: microwave freeze drying, pretreatment, pore network structure, Chinese yam, porosity DOI: 10.25165/j.ijabe.20201304.5605 Citation: Wang H, Duan X, Zhao L J, Duan L L, Ren G Y. Effects of different pretreatments on the pore structure of Chinese yam during microwave freeze drying. Int J Agric & Biol Eng, 2020; 13(4): 232–237.